The Correlation Between Dietary Habits and Physical Activity with the Somatotype of Game Sports Athletes - Defriani Dwiyanti; Hasneli Hasneli; Khairunnisa Khairunnisa (JUARA : Jurnal Olahraga, 2021)
One of the factors that support an athlete's success in a match includes the compatibility of somatotype with the sport. This study aimed to determine the correlation between dietary habits and physical activity with the somatotype of game sports athletes. The design is a cross-sectional study. The study was held from February 2019 until May 2020. Sampling is using comprehensive selection which the samples amounted to 37 athletes. Anthropometric measurements carried out research data collection, interviews using the SQ-FFQ form, and Baecke physical activity scale questionnaire. Data were analyzed by univariate and bivariate. The results showed that most soccer athletes (94.1%) and all takraw athletes (100%) have unsuitable somatotype categories, most soccer athletes (82.4%), and all takraw athletes (100%) have severe physical activity. Most soccer athletes (76.5%) and more than half of takraw athletes (55%) have poor dietary habits. The average somatotype of respondents is ectomorph, with the body's unique characteristics that tend to be thin. When intake is less than intake requirements, strenuous physical activity can cause the body to grow to be light. Respondents are advised to consume information as intake requirements to adjust the training scheme by adding weight training to the forming of athlete's muscle mass and to place nutritionists in PPLP.